2015
DOI: 10.1302/0301-620x.97b9.34910
|View full text |Cite
|
Sign up to set email alerts
|

Use of leucocyte esterase reagent strips in the diagnosis or exclusion of prosthetic joint infection

Abstract: Infection is a leading indication for revision arthroplasty. Established criteria used to diagnose prosthetic joint infection (PJI) include a range of laboratory tests. Leucocyte esterase (LE) is widely used on a colorimetric reagent strip for the diagnosis of urinary tract infections. This inexpensive test may be used for the diagnosis or exclusion of PJI. Aspirates from 30 total hip arthroplasties (THAs) and 79 knee arthroplasties (KA) were analysed for LE activity. Semi-quantitative reagent strip readings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 25 publications
0
22
1
1
Order By: Relevance
“…This observation was first made by Parvizi et al [6], finding that 11.6% (17 of 147) of samples were unreadable because of blood. Subsequent studies verified this rate of invalid results, finding invalid test strip rates of 29.2% [7], 17% [5], and 9.5% [1]. Because of the high rate of blood interference, it has been suggested that the sample is centrifuged to remove blood cells before the fluid is placed on the test strip [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This observation was first made by Parvizi et al [6], finding that 11.6% (17 of 147) of samples were unreadable because of blood. Subsequent studies verified this rate of invalid results, finding invalid test strip rates of 29.2% [7], 17% [5], and 9.5% [1]. Because of the high rate of blood interference, it has been suggested that the sample is centrifuged to remove blood cells before the fluid is placed on the test strip [12].…”
Section: Discussionmentioning
confidence: 99%
“…The original report on the utility of LE by Parvizi et al [6] found that a (þþ) LE cutoff provided 80.6% sensitivity in diagnosing PJI. Although there are a few centers reporting a higher sensitivity for the urinary LE test strip [10,11], most centers have reported lower values, including sensitivities of 69% [5], 66% [9], 81% [1], 84.21% [2], 75% [3], and 84% [4]. A recent large retrospective study of tests for PJI including the erythrocyte sedimentation rate, C-reactive protein, WBC count, polymorphonuclear neutrophil percentage, and LE found that LE had the lowest sensitivity of all tests [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weiterhin kann in das Gelenkpunktat ein Leukozytenesteraseteststreifen gehalten werden, wie es für den Urinstatus bekannt ist. Für die Diagnostik am Knie-und Hüftgelenk werden Sensitivitäten zwischen 69 und 81 % sowie Spezifitäten zwischen 93 und 100 % angegeben [27][28][29]. Allerdings waren zwischen 17 und 30 % der Proben aufgrund von Blutbeimengungen des Punktats nicht ablesbar.…”
Section: Testverfahren Beim Spätinfektunclassified